Enhancing creative thinking skills on biotechnology materials: Development of an e-module using Google Sites - Setiani, Indra; Sajidan, Sajidan; Fatmawati, Umi (Universitas Negeri Yogyakarta, 2025)
Updates are not yet available for media learning based on electronic learning, which loads creative learning on biotechnology material and has an impact on boring lessons. Therefore, this study aims to: 1) Determine the validity of e-modules on biotechnology material to improve students' creative thinking skills; 2) determine the effectiveness of e-modules on the material to improve students' creative thinking skills; 3) determine the practicality of e-modules on the material to improve students' creative thinking skills. Development research e-modul with using google site on this biotechnology material using model procedures development of ADDIE (Analysis, Design, Development, Implementation and Evaluation) with a sample size of 95 students to test its effectiveness. The research results show that: 1) Products E- Module Biotechnology use google sites are very valid for improving students' creative thinking skills semester 3 Program Studies Education Biology with proven mark validity as big as 86.36% from media expert, 93.75% from the expert material, And 81.94% from the test try group scale small. 2) Product E- Module Biotechnology use google very sites effective For increase skills think creative student semester 3 Program Studies Biology Education is proven by the significance value of the Wilcoxon test of 0,000 in lower 0.05; 3) Products E- Module Biotechnology use google very sites practical For increase skills think creative student semester 3 Program Studies Biology Education with proven mark its practicality as big as 88.18% of the questionnaires were filled out by students in the group scale large. So, in general, the Google Site-based e-module product on biotechnology material is worthy of use and dissemination. Further research recommendations to be able to research Google Sites based E-Modules using different materials and variables.